Analisis Kesesuaian Akad dalam Praktik Pembiayaan BMT terhadap Prinsip Hukum Islam - Moh Ridwan Al Murtaqi (https://journal.metanusantara.com/jenius/index.php/jem, 2025)
The growth of Baitul Maal wat Tamwil (BMT) as an Islamic microfinance institution in Indonesia shows the increasing needs of the community for financing that is in line with Islamic principles. Behind this progress, questions arise about the extent to which the contracts used are truly in accordance with Islamic law, both legally-formally and substantively. This study aims to analyse the suitability of contracts in financing practices in BMTs with the principles of Islamic law and identify the implementative obstacles faced. This study uses a qualitative approach with a normative-empirical method. Data were collected through in-depth interviews and observations of contract practices in several BMTs, with the main informants including financing managers, Sharia Supervisory Board, and customers. The results show that the most dominant type of contract is murabahah, followed by mudharabah, musyarakah, and ijarah. Although administratively they have been prepared in accordance with sharia guidelines, in practice there are discrepancies, especially in the implementation of murabaha, which has not fully fulfilled the principles of ownership and responsibility of goods. Profit-sharing agreements have also not been widely applied due to limited managerial capacity.